Self-tuning and the cosmological constant problem - Ghataore, Sukhraj Singh (2023)
The cosmological constant problem is one of the biggest theoretical hurdles of the modern age. It comes out of two great theories in physics: General Relativity (GR) and Quantum Field Theory (QFT). QFT predicts the existence of vacuum energy and GR predicts that it will gravitate like a cosmological constant, Λ_{vac}. Through observations we find that the Universe is undergoing an accelerated expansion which can be sourced by a constant term, Λ_{obs}, whose value is set by observations. Therefore it would be tempting to compare Λobs with Λ_{vac}, but through this we find that the predicted value of the vacuum energy is far, far greater than that of observation. In fact, at a lower estimate it represents a fine-tuning of∼ 10^{36} orders of magnitude. However, this is not the full extent of the problem. Even if we accept a fine-tuning in Λ_{vac}, its value is unstable to higher order perturbations, leading to repeated fine-tunings and re-tunings. This is known as radiative instability of the vacuum, and it is the true source of the cosmological constant problem.